1994
DOI: 10.7863/jum.1994.13.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Infected renal cysts: sonographic diagnosis and management.

Abstract: IRC are rare entities characterized by fever and unilateral flank pain resistant to antibiotic therapy. In our series of nine IRC in eight patients, the predominant sonographic finding was an abnormal echogenic texture of the cyst contents, in contrast to previous reports that stressed the frequency of wall thickening as a sign of infection. Sonographically guided cyst aspiration and drainage of eight cysts in seven patients provided diagnostic material and resulted in relief of symptoms. Although the cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The clinical diagnosis of superimposed infection of a renal cyst is difficult because typically specific symptoms and pyuria are absent. It is difficult to differentiate an infected simple renal cyst from an abscess both clinically and radiologically [35,76,77]. An infected cyst may also mimic a renal cyst complicated by intracystic haemorrhage on imaging studies.…”
Section: Infected Cystmentioning
confidence: 99%
“…The clinical diagnosis of superimposed infection of a renal cyst is difficult because typically specific symptoms and pyuria are absent. It is difficult to differentiate an infected simple renal cyst from an abscess both clinically and radiologically [35,76,77]. An infected cyst may also mimic a renal cyst complicated by intracystic haemorrhage on imaging studies.…”
Section: Infected Cystmentioning
confidence: 99%
“…Renal cyst infection is a rare complication, accounting for only 2.5% of all events [5]. The clinical presentation and imaging findings are nonspecific, making diagnosis challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Infections involving the cysts are often refractory to the antibiotic therapy because of limited entry of commonly used antibiotic into the cysts. Treatment of infected cysts in ADPKD should begin with lipophilic compounds such as ciprofloxacin and new quinolones, TMP-SMX, because of their low toxicity and high volume of distribution [1-4]. In the lack of response to the antibiotic therapy, cyst drainage may be a suitable alternative method.…”
Section: Discussionmentioning
confidence: 99%
“…It should be considered that the identification of infected cysts is essential for imaging-guided diagnostic or therapeutic percutaneous puncture. US may be a feasible method for the evaluation of complicated cysts in ADPKD however it often fails to reliably differentiate benign hemorrhagic cysts from the other complications [4]. Chapman et al [1] suggested that percutaneous drainage under fluoroscopic localization should be the treatment of choice for the accessible infected cysts greater than 5 cm in diameter.…”
Section: Discussionmentioning
confidence: 99%